2016
DOI: 10.1002/acp.3297
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Culture on Goal Perception: Qatar Versus Denmark

Abstract: Expectations of control put forth by societal norms impose a constant influence on goal perception. To examine the influence of culture on perception of personal goals, 124 Middle Easterners and 128 Scandinavians rated their perceived locus of control, generated goals and evaluated goal characteristics. Findings show several cultural and gender differences, most notably in perceived locus of control, unhappiness despite goal achievement and adherence to cultural life script. Many differences were qualified by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 77 publications
(135 reference statements)
0
5
0
Order By: Relevance
“…This finding was replicated by Ottsen et al, (2016) who found that men in Qatar perceived more external control by powerful others and by chance than Qatari women (all ps <.006). The Danish sample, however, showed no significant gender difference on any of the scales (all ps >.316).…”
Section: Attribution Of Control Across Gender and Culturementioning
confidence: 68%
See 4 more Smart Citations
“…This finding was replicated by Ottsen et al, (2016) who found that men in Qatar perceived more external control by powerful others and by chance than Qatari women (all ps <.006). The Danish sample, however, showed no significant gender difference on any of the scales (all ps >.316).…”
Section: Attribution Of Control Across Gender and Culturementioning
confidence: 68%
“…All participants completed the multidimensional locus of control scale (Levenson, 1981). This scale is ideal for cross-cultural exploration because data from societies that differ on the individualism index gain validity from a construct that measures internal control and external control on separate dimensions (Cheng, Cheung, Chio, & Chan, 2013;Ottsen et al, 2016). The multidimensional locus of control scale addresses the participant's attribution style: their subjective appraisal of factors that account for the outcome of events in their life.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations